2022
DOI: 10.33560/jmiki.v10i2.480
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Penyebab Pending Claim Ranap JKN Dengan Fishbone Diagram Di Rsup DR Kariadi

Abstract: Pembiayaan kesehatan di rumah sakit diperoleh dari pembayaran klaim oleh BPJS Kesehatan. BPJS Kesehatan melakukan purifikasi dan verifikasi berkas klaim. Berkas klaim yang dinyatakan tidak lengkap oleh BPJS Kesehatan, menyebabkan pending claim yang berdampak keterlambatan pembayaran klaim. Berdasarkan studi pendahuluan di RSUP Dr Kariadi ditemukan permasalahan penyelenggaraan klaim JKN yakni pending claim 3,67%. Penelitian dilakukan bertujuan menganalisis faktor penyebab pending claim rawat inap JKN di RSUP Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In addition, the coder's skill in determining the diagnosis code and action can affect pending claims. A previous study confirmed this finding, saying that coding officers who have a more extended working period show better productivity because officers a more extended active period, the level of skill, knowledge, and analytical ability in coding increases, and the resulting coding is more accurate (Sahir & Wijayanti, 2022).…”
Section: Internal Factors Causing Pending Social Health Insurance Adm...mentioning
confidence: 55%
See 1 more Smart Citation
“…In addition, the coder's skill in determining the diagnosis code and action can affect pending claims. A previous study confirmed this finding, saying that coding officers who have a more extended working period show better productivity because officers a more extended active period, the level of skill, knowledge, and analytical ability in coding increases, and the resulting coding is more accurate (Sahir & Wijayanti, 2022).…”
Section: Internal Factors Causing Pending Social Health Insurance Adm...mentioning
confidence: 55%
“…The claim administration verification process is carried out by verifying the suitability of the claim file with the required files. If there are discrepancies, the file is returned to the hospital for completion (Sahir & Wijayanti, 2022).…”
Section: Billing Discrepancy With Medical Resumementioning
confidence: 99%